Mathematical Approximation of Single and Double-Sided Truncated Normal Distribution Using Logistic Function - Hamasha, Mohammad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This article provides a mathematical approximation model of the general double-sided truncated normal distribution. The right and left-sided cases are included in the model as special cases. The double-sided truncated normal distribution is important for many applications in industrial and systems engineering. For example, in quality control, production engineers maybe interested in scrapping the unfit products. The distribution of product variations after this scrapping is basically double-sided truncated normal distribution. A full analysis of deviation of the introduced approximation’s results from the actual results is provided. Further, recommendations for the use of the model are provided.